Customer service: a management strategy for increasing organizational competitiveness in Valledupar companies (Colombia). - Daza-Rodríguez, María Eugenia; Daza-Porto, Maritza Isabel; Pérez-Orozco, Adith Bismarck (AiBi Journal of Research, Administration and Engineering, 2017)
Customer service is currently a topic of relevance in organizations, it depends on the attraction and retention of customers, whether internal or external. In addition, the most important strategy with which senior management can be committed is the creation of a culture of customer service in the company's employees, as a guideline in the execution of its activities. The objective of this article is to present the results of a research aimed at reflecting on the impact of customer service on increasing competitiveness in companies in Valledupar, Colombia. The analysis is made from a bibliographic review of authors such as: Chiavenato (2002), Gómez (2011) Najul (2011), Robbins (2010), David (2010), Pizzo (2013), among others. The type of research is descriptive rather than experimental, and the results are presented from a reflective perspective. The research design is based on field work by direct observation in organizational segments, such as clothing stores, restaurants, and health care centers. The results show that the perception about the little culture of customer service affects the productivity and economy of the Valledupar organizations; However, explicit models are established for the implementation of a quality customer service, as well as the analysis of how the organizational climate influences the success of this strategy.
Keywords: Customer service, management strategy, competitiveness, organizational culture, work climate.